Anxiety and depression predict quality of life in Turkish patients with systemic lupus erythematosus - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2015)
Objective The aim of our study was to evaluate quality of life (QoL) in patients with systemic lupus erythematosus (SLE) and assess the impact of disease activity and psychological distress on health-related quality of life (HRQoL) in Turkey. Methods The Medical Outcomes Study Short Form (SF) -36 was used in a cohort of 113 consecutive patients with SLE and 123 age- and gender-matched healthy subjects to measure HRQoL. Patients' disease activity was assessed with SLE disease activity index (SLEDAI) and psychological distress was evaluated by the Hospital Anxiety and Depression Scale (HADS) for all participants. Patients' demographic and clinical data were recorded at the time of HRQoL and HADS testing. Multiple logistic regression analysis was performed to explore the relationships between demographics, disease duration, disease activity as well as psychological (anxiety and depression) variables and the HRQoL. Results SLE patients have lower quality of life than healthy controls. No relationship between HRQoL and SLE activity or disease duration were observed. Patients with anxiety and/or depression reported worse SF-36 scores than those without psychological distress. The results of multivariate analysis suggested that HADS-A, HADS-D scores and working status were associated with the impairment of HRQoL. Conclusion HRQoL is impaired in patients with SLE and is associated with mood disorders. Physicians should pay close attention to detect anxiety and depression and manage them in order to improve the quality of life in patients with SLE.
Keywords: systemic lupus erythematosus; quality of life; anxiety; depression; HEALTH SURVEY SF-36; DISEASE-ACTIVITY; HOSPITAL ANXIETY; ITALIAN PATIENTS; OUTCOMES; RHEUMATOLOGY; DETERMINANTS; DISCORDANCE; PHYSICIANS; DISORDERS